2014
DOI: 10.1002/job.1953
|View full text |Cite
|
Sign up to set email alerts
|

Weekly work–school conflict, sleep quality, and fatigue: Recovery self‐efficacy as a cross‐level moderator

Abstract: SummaryThis study employed a weekly diary method among a sample of 74 Midwestern college student workers in order to examine the within-person relationships between work-school conflict, sleep quality, and fatigue over five weeks. Further, recovery self-efficacy was proposed as a cross-level moderator of the relation between sleep quality and fatigue. Results from multilevel analyses demonstrated that weekly work-school conflict was negatively related to weekly sleep quality and positively related to end-of-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 58 publications
2
44
0
1
Order By: Relevance
“…For example, ten Brummelhuis and Bakker () found that evening detachment mediates the link between evening physical activities and next‐day vigor, whereas relaxation does not significantly mediate this relationship. Also, work by Pereira et al () did not support recovery experiences (i.e., detachment, relaxation, mastery, and control) as mediators between physical activities and health improvement during vacation. Likewise, in the sleep literature, it is not clear whether exercise induces better or more sleep (Driver & Taylor, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, ten Brummelhuis and Bakker () found that evening detachment mediates the link between evening physical activities and next‐day vigor, whereas relaxation does not significantly mediate this relationship. Also, work by Pereira et al () did not support recovery experiences (i.e., detachment, relaxation, mastery, and control) as mediators between physical activities and health improvement during vacation. Likewise, in the sleep literature, it is not clear whether exercise induces better or more sleep (Driver & Taylor, ).…”
Section: Discussionmentioning
confidence: 90%
“…The cumulative benefits of physical activities through both physiological and psychological mechanisms may manifest after the periods of respites. Accordingly, time‐lagged assessments may be required so that both the physiological and psychological benefits of exercise are fully experienced (e.g., Feuerhahn et al, ; Pereira, Iseli, & Elfering, ). Given the weak or nonsignificant effects of day‐level exercise on NA in the previous literature, we expect that our weekend timeframe will be a longer time window to capture a wider variability of physical activities and allow the recovery benefits to fully manifest.…”
Section: Weekend Physical Activity and Post‐weekend Namentioning
confidence: 99%
“…Studies have shown that job hours and workload have been associated with work‐school conflict in respect of the limited time to meet work and school demands [Markel and Frone, ]. In turn, work‐school conflict has been associated with poor sleep quality and fatigue [Park and Sprung, ], which may increase the risk for work injury [Kling et al, ; Arlinghaus et al, ]. Students are also protected by legislation regarding working hours and shift work.…”
Section: Methodsmentioning
confidence: 99%
“…In most of the studies (Ladebo and Awotunde, ; König et al, ; Nauta et al, ; Lightsey et al, ; Park and Sprung, ; Hsieh et al, ) that looked at the moderating role of self‐efficacy, there was an investigation of the relationship between a stressor and a strain. As Siu et al .…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies (Ladebo and Awotunde, 2007;König et al, 2010;Nauta et al, 2010;Lightsey et al, 2013;Park and Sprung, 2015;Hsieh et al, 2016) that looked at the moderating role of self-efficacy, there was an investigation of the relationship between a stressor and a strain. As Siu et al (2007) argued previously, general self-efficacy can be thought of as more of a personal resource or a vulnerability factor.…”
Section: Introductionmentioning
confidence: 99%